The Cervical Cancer Research Network (Gynecologic Cancer InterGroup) roadmap to expand research in low- and middle-income countries. Issue 5 (25th February 2021) - McCormack, Mary; Gaffney, David; Tan, David; Bennet, Kathy; Chavez-Blanco, Adriana; Plante, Marie
Abstract : Cervical cancer is a global health problem which disproportionally affects women in low- and middle- income countries. The World Health Organization recently launched its global strategy to eliminate this disease in the next two decades. For those women diagnosed today with cervical cancer better strategies are needed to improve outcome and reduce treatment-related morbidity. Clinical trials are critical to shaping future treatment, and much has been achieved already. However, such opportunities are limited in low resource settings, and the Cervical Cancer Research Network is dedicated to expanding access to new technologies in surgery, radiation, and medical oncology. In this article we review the status of the trials portfolio and outline future objectives, including the launch of a number of research grants for aspiring or established researchers in low- and middle-income settings